Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1097/01.prs.0000295972.18570.0b
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Herbal Medicines on Platelet Function: An In Vivo Experiment and Review of the Literature

Abstract: The herbal medicines investigated in this study do not affect platelet function in vivo. Neither this experiment nor a review of the literature supports the concern of perioperative bleeding in users of these herbal medicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 43 publications
0
55
1
2
Order By: Relevance
“…The investigators of this recent review postulate that antiplatelet actions, as well as interference with warfarin, could put cancer patients at risk. However, when commercially available extracts of ginkgo, garlic, Panax ginseng, St. John's wort, and saw palmetto were given to 10 healthy volunteers for 2 weeks, no effect on platelet activity was demonstrated [52]. Likewise, evidence of interaction of warfarin with herbs is based largely on case reports of variable (mostly poor) quality, which is not confirmed by pharmacologic studies [53].…”
Section: Risks Of Alternative Cancer Carementioning
confidence: 99%
“…The investigators of this recent review postulate that antiplatelet actions, as well as interference with warfarin, could put cancer patients at risk. However, when commercially available extracts of ginkgo, garlic, Panax ginseng, St. John's wort, and saw palmetto were given to 10 healthy volunteers for 2 weeks, no effect on platelet activity was demonstrated [52]. Likewise, evidence of interaction of warfarin with herbs is based largely on case reports of variable (mostly poor) quality, which is not confirmed by pharmacologic studies [53].…”
Section: Risks Of Alternative Cancer Carementioning
confidence: 99%
“…In addition, it has been reported that enough concentrations of allicin, a primary constituent of garlic (Allium sativum) can result into platelet aggregation and degranulation blockage. Despite of in vitro studies, it is noted that after administration of these plants in healthy individuals, the platelet function does not change (Beckert et al, 2007).…”
Section: Effects On Platelet Activitymentioning
confidence: 99%
“…The efficacy and safety of herbal preparations are not always clearly defined though, and the use of these may cause increased perioperative bleeding risk due to disrupted coagulation (Beckert et al, 2007). Whether these preparations have direct effects on the coagulation system or cause disruption due to drug interactions is not always known (Beckert et al, 2007). Plants studied for effects on coagulation in vitro and/ or in vivo, as well as possible bioactive constituents, are listed in Table 1.…”
Section: Herbals and Their Effect On Blood Parametersmentioning
confidence: 99%
“…Harmane-and harmine-induced reduction of tyrosine phosphorylation limits calcium mobilization and arachidonic acid liberation, which decreases platelet aggregation . The coagulation cascade is attenuated by various phytochemicals such as polyphenols, sulfated polysaccharides, lapachol, allicin, and thiosulfates through inhibition or decreased activity of tissue factor (Lee et al, 2003(Lee et al, , 2004, thrombin (Medeiros et al, 2008;Zhang et al, 2008), vitamin K-epoxide reductase (Preusch & Smalley, 1990), plasminogen activator, phospholipase, thromboxane A 2 , lipoxygenase (Srivastava, 1986;Beckert et al, 2007), thiol enzymes (coenzyme A and 3-hydroxy-3-methylglutaryl coenzyme A reductase) (Liao & Li, 1997), and other clotting factors, as well as potentiation of heparin co-factor II (Medeiros et al, 2008;Mao et al, 2009), and increased fibrinolysis. Coumarin compounds have the ability to affect coagulation through scavenging of reactive oxygen species, inhibiting cyclic nucleotide phosphodiesterases, inhibiting the activity of vitamin K-dependent γ-carboxylase (activation of coagulation factors) and prostaglandin synthesis (Hoult & Paya, 1996;Coppinger et al, 2004).…”
Section: Herbals and Their Effect On Blood Parametersmentioning
confidence: 99%